KAJIAN PENGGUNAAN MEDIA AJAR BERBASIS CANVA DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SD NEGERI 138 PALEMBANG - Nova Fitria Ningsih; Dwi Styaningrum; Koria Amilia; Marhamah (STKIP Subang, 2026)
ABSTRACT This study aims to assess the use of Canva-based learning media in improving learning motivation at SD Negeri 138 Palembang. The basis of this study is the low learning motivation of students and the need for more engaging, visual, and interactive learning media at the elementary school level. The method used is qualitative-descriptive with analysis based on literature review. The findings indicate that Canva has high potential in improving student learning motivation because it can present material in a more engaging and easy-to-understand way. Previous findings also support that the use of Canva has a positive impact on student motivation and engagement in the learning process.